A computational software for Photovoltaic systems design focusing on building applications - Mantzaris, Dimitrios Charalampos (IJRDO-Journal of Applied Science, 2018)
Solar radiation energy is one of the most important energy sources with increasing penetration into the power supply systems of many countries, due to the reduced environmental impact of its operation. This study introduces a software providing a complete study of a photovoltaic infrastructure at a given location of PV grid and a specific consumption of electric power in residential buildings. The application includes all the stages of a PV installation study, starting at the location of PV grid installation, calculating the radiation, determining the electricity consumption, determining the installation self-sufficiency, selecting PV modules, identifying the inverters, the accumulators and the wiring, and, finally, of PV modules’ dimensioning - placement. This computational software contributes to the science of photovoltaic technologies as new photovoltaic elements with improved characteristics can be studied and developed, because it is possible to register in software of characteristic specifications beyond the standard commercial elements.